Clinal variation as a tool to understand climate change - Mayekar, Harshad Vijay; Ramkumar, Durga Kavya; Garg, Divita; Nair, Abhishek; Khandelwal, Ashwin; Joshi, Kavya; Rajpurohit, Subhash (Frontiers in Physiology, 2022)
Clines are observable gradients that reflect continuous changes in the biological traits of species across geographical ranges. They can be both genotypic and phenotypic in nature. Various phenomena promote the formation of clines, which includes selection and gene flow between two forms of life that are separated by migration, space, or are targets of natural selection. The extent of variation reflects the gradient of the cline. The focus of this review is to study the interactions between geographical variations in traits and climatic variables and use it as a tool to understand organismal responses to climate change. Clinal variations are active genomic responses at the population level and provide an immense power to address questions related to warming. In recent times it is evidenced that populations are responding to climate change way faster than expected i.e. they adapt rapidly and this adaptation has been recorded at the allelic levels as well. This review primarily takes into account ectotherms and particularly drosophilid flies. We discuss traits associated with clinal variation at the phenotypic level as well as their underlying genetic regulators. Given prevailing climatic conditions and future projections for climate change, clines could emerge as monitoring tools to track cross-talk between climatic variables and organisms.